ANALISIS MITIGASI RISIKO USAHA KOPI ROBUSTA PADA KOPI LEDUG, KECAMATAN PRIGEN, KABUPATEN PASURUAN - Andriani, Catherine; Winarno, Sri Tjondro; Rizkiyah, Noor (Journal of Management Small and Medium Enterprises (SMEs), 2024)
Currently, the coffee sales business is increasing. Kopi Ledug is one of the businesses engaged in selling coffee and has a business activities process and every business process has risks that can harm the company. Market demand that does not match the estimate is one of the risks that can harm the company financially. This study aims to identify risks and conduct risk assessments and determine risk mitigation strategies to overcome the causes of emerging risks. The methods used are House of Risk and Pareto Diagram. The results of House of Risk Phase 1 show that there are 25 risk events and 25 risk agents that occur during the business process. Pareto Diagram shows the results of 14 risk agents that are prioritized. The results of House of Risk Phase 2 show that there are 16 mitigation actions that can be implemented by Kopi Ledug in overcoming risks. Keywords: Risk; Mitigation; House of Risk; Pareto Diagram; Robusta Coffee